The unevenness of respiratory rhythm as an indicator of emotional stress - Yu. E. Vagin (Сеченовский вестник, 2022)
External respiration consists of relatively independent cycles. During each breath cycle the respiratory center makes a decision about how to meet the respiratory necessity of the body. The infl uence of previous respiratory cycles for the next leads to the formation of the breath cycles continuum.The method was developed for analysis of unevenness of respiratory rhythm, which takes into account the relative independence of each breathing cycle and the impact of previous respiratory cycles later. It was found that the unevenness of respiratory rhythm refl ects the degree of emotional stress and is not associated with the physical strain of the organism. The uneven rhythm of breathing increased when dietary behavior, mental activity, pain reactions, acute emotional stress, fatigue in real productive activity. Uneven breathing rhythm changed unilaterally with blood pressure (r=0.66) and galvanic skin response (r=0.81). Uneven breathing rhythm changed from 0 to 20 % in diff erent functional states of the body. The increasing irregularity of the rhythm of breathing more than 30 % was short-lived, and was a harbinger of the imminent death of the body. The unevenness of respiratory rhythm was possible to predict the survival of animals in acute experimental emotional stress. Assessment of the degree of analgesia using the uneven rhythm of breathing helped to develop the microwave refl ex therapy. Study of the uneven breathing rhythm in actual work activity contributed to the prevention of the workers morbidity. The hunger motivation in humans was investigated in olfactory stimuli with the unevenness of breathing rhythm. The unevenness of respiratory rhythm has characterized the magnitude of the animals’ emotional reactions over itself stimulation of the brain.